Factors influencing the development of the creative film industry in Batam city - Jupriyatmoko, Jupriyatmoko; Wangdra, Yvonne (Jurnal Ekonomi, 2024)
The industrial development in Batam City, still dominated by the manufacturing sector, shipyards, and construction, necessitates the growth of new industries, one of which is the creative industry such as film. This research aims to 1) Evaluate the impact of Film Genre on the Film Industry in Batam City, 2) Analyze the influence of Film Distribution on the Film Industry in Batam City, 3) Measure the influence of Film Censorship on the Film Industry in Batam City. The study employs a quantitative approach with the population of Batam City residents and a sample of 386 respondents selected through random sampling. Data collection methods involve observation, questionnaires, and documentation. The research findings conclude that: 1) Film Genre has a significant impact on the Film Industry partially, 2) Film Distribution significantly influences the Film Industry partially, 3) Film Censorship has a significant partial impact on the Film Industry, 4) Collectively, Film Genre, Distribution, and Censorship have a positive and significant impact on the Film Industry in Batam City. Statistical test results show a regression coefficient of 5.544, with a t-test yielding a value of 6.193 and a significance level of 0.000 (α < 0.05). Additionally, the F-test reaches a value of 216.138, indicating that the F-value is greater than the F-table (216.138 > 2.24). Thus, the hypothesis of this study is accepted.